The Effect of Principal's Leadership and Participation of the Industry World on the Quality 0f State Vocational Schools - Aris Wiratmoko; Masduki Ahmad; Desi Rahmawati (STAI Hubbulwathan Duri, 2021)
The quality of students graduating from vocational high school can be improved if the principal's leadership and increased industrial participation are supported. The purpose of this study is to analyze. This study employs a quantitative approach and path analysis techniques in conjunction with a survey method. The data collection instrument is a questionnaire. Instruments were thoroughly tested prior to their use in research. Validity and reliability tests are conducted on the instruments. The data analysis in this study was conducted using both descriptive and inferential statistical techniques. This study was conducted at seven State Vocational High Schools in Serang City. Principals' leadership and industrial participation, according to research, have a direct effect on school quality. The principal's leadership directly impacts the school's quality. Industry involvement has a direct positive effect on the quality of education. Principal leadership has a positive effect on labor participation directly. This research implies a shift in perspective regarding the quality of State Vocational Schools in Serang City, particularly at the leadership level as a manager accountable for the graduates' quality. School leaders ensure that collaboration with industry is demonstrated through participation in the development of industry-related curricula.